1993
DOI: 10.1080/01919512.1993.10555731
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Ozone On The Production Of Biodegradable Dissolved Organic Carbon (BDOC) During Water Treatment

Abstract: This article deals with the oxidation effect of ozone on the increasing fraction of biodegradable organic matter with the "ozotest" method, a laboratory technique which simulates the effect of ozonation and allows a complete oxidation assessment. Ozone treatment was performed on river water samples and sand filter effluent samples. Ozone consumption, reduction of UV absorbance and BDOC formation were monitored with applied ozone doses from 0 to 10 mgR and with contact times from 0 to 60 min. The BDOC formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 5 publications
5
32
0
Order By: Relevance
“…The microorganisms use organic compounds, both dissolved in water and previously adsorbed onto the carbon, in their metabolic processes, which results in the recovery of the adsorption capacity of the GAC. As a result, the application of ozonation followed by BGAC leads to biologically stable water [6,19,29]. However, there are still some doubts about the mechanisms of the NOM removal and the THMs control by the simultaneous use of ozone and BGAC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microorganisms use organic compounds, both dissolved in water and previously adsorbed onto the carbon, in their metabolic processes, which results in the recovery of the adsorption capacity of the GAC. As a result, the application of ozonation followed by BGAC leads to biologically stable water [6,19,29]. However, there are still some doubts about the mechanisms of the NOM removal and the THMs control by the simultaneous use of ozone and BGAC.…”
Section: Introductionmentioning
confidence: 99%
“…BDOC that is produced by ozonation can be removed in subsequent biological treatments. However, Volk et al [19] and Wricke et al [20] reported that the maximum BDOC production by ozonation was only around 30% of the total DOC in raw water, even if the ozone dose or reaction time was increased. The ozonation should be set to achieve treatment goals that are based not only on the characteristics of the NOM in the raw water, which optimizes biofiltration, but also on economic benefits [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally the concentrations of BDOC analysed with dynamic method in glass column system with attached biofilm were calculated as the difference in concentration of DOC between the inlet water sample in column system and the effluent water sample with lowest concentration of DOC, namely DOC BAC and DOC min (Fig. 3) based on the definitions developed by other researchers (Fahmi et al, 2003;Hammes and Vital, 2008;Volk et al, 1993;Ribas et al, 1991 andYavich et al, 2004) and in this study called BDOC BAC . The total concentration of BDOC (namely BDOC total ) which accounts for both parts -quantity of biodegradable part in sample (DOC BAC ) and LOC (DOC LOC ) was not considered in this paper since it was not comparable with measurements of BDOC in WTP.…”
Section: Resultsmentioning
confidence: 99%
“…During ozonation dissolved organic carbon (DOC) is transformed to biodegradable organic carbon (BDOC), which then is metabolized by bacteria in the biofilter (Fahmi et al, 2003;Hammes and Vital, 2008;Volk et al, 1993). The amount of BDOC fraction depends on the type of natural organic matter (NOM) present in the water (Huck, 1990;Kaplan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%